If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-1x + 6) = 18 Reorder the terms: (6 + -1x) = 18 Remove parenthesis around (6 + -1x) 6 + -1x = 18 Solving 6 + -1x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 18 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 18 + -6 -1x = 18 + -6 Combine like terms: 18 + -6 = 12 -1x = 12 Divide each side by '-1'. x = -12 Simplifying x = -12
| -10+5x+49+90=180 | | 1-4X=7-25 | | (8w+3)(5w-15)=0 | | (5z+8)(2-z)=0 | | -35+5x=x+77 | | 4a^2-12a+8= | | 112c-3= | | 8x+3=8x+72 | | 5(x+5)=5(x+.6) | | 60+30x+90=180 | | f(x)=x^2-10x-4 | | 13k-4= | | n+8+2(n+4)=64 | | 9x+6y=25 | | 5*n=-30 | | 4x+3=-13-4x | | -4p+3(6-4p)=-94 | | 2x^2-8x+1=y | | 11x-7y=-4 | | 3n+2+4n+3=47 | | 30=-4.9t^2+27t+2.4 | | 2(x+5)-4=3x+10 | | 90+x+44++55=180 | | 4-7y=11-4.2y | | 12=-2x+4 | | -131+10x=-2x+121 | | x^2+4x-7=y | | 120=-4(-8x-6) | | 2g+15=10(-4g+1) | | 3y+20=14+5y | | 2(4-3x)=x+3(x-2) | | 5k+20=9k-4 |